PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PERTUMBUHAN LABA PADA PT PEGADAIAN (PERSERO) KANWIL II PEKANBARU - Desi Yuliana; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to partially and simultaneously examine th effect of liquidity and solvency on earnings growth. In this study the independent variables are liquidty and solvency, while the dependent variable is earnings growth. The sample used is secondary data derived from th company’s financial statements that are seen every month in the period 2014 to 2018. Data analysis using simple linear regression analysis, multiple linear regression analysis, t test, F test, and the coefficient of determination test processed using SPSS 23. The result showed that the partial liquidity variable had no effect on earnings growth, whil the solvency variable partially influences earnings growth. Simultaneous test reults indicate that there is an influences of liquidity and solvency variables on earnings growth in PT. Pegadaian( Persero) Regional Office II Pekanbaru.Keyword : Earnings Growth, Liquidity, Solvency.